Electromagnetic wave scattering by small impedance particles of an arbitrary shape - Ramm, Alexander G. (My University, 2013)
Scattering of electromagnetic (EM) waves by one and many small (ka≪1) impedance particles D[subscript m] of an arbitrary shape, embedded in a homogeneous medium, is studied. Analytic formula for the field, scattered by one particle, is derived. The scattered field is of the order O(a [superscript 2−κ] ), where κ∈[0,1) is a number. This field is much larger than in the Rayleigh-type scattering. An equation is derived for the effective EM field scattered by many small impedance particles distributed in a bounded domain. Novel physical effects in this domain are described and discussed.
Keywords: Electromagnetic waves; Wave scattering by small body; Boundary impedance; Many-body wave scattering; Wave scattering